Studies on Attributes of Hair and Production Potential of Camel Reared in Semi-intensive Management System - Bhakat, Champak; Mehta, S C; Sahani, M S (Annals of Arid Zone, 2016)
Annual hair yield data from 1038 Indian dromedary camels of 3 breeds(Bikaneri, Jaisalmeri and Kachchhi) from 5 different age groups were recorded.The Bikaneri breed of camel produced significantly (P